Stereoselective Catalytic Synthesis of Tetrasubstituted Olefins from the Intermolecular Conjugate Addition of Simple Alkenes to α,β-Unsaturated Carbonyl Compounds() - Kwon, Ki-Hyeok (2011)
Recent efforts in designing expeditious catalytic synthesis of tetrasubstituted olefins have in part been stimulated by growing needs for developing generally applicable methods for tamoxifen analogs (anti-breast cancer drug) as well as for photo-responsive organic materials and molecular devices.([1]) A number of different catalytic methods have been developed to synthesize tetrasubstituted olefins, including: Suzuki-type Pd-catalyzed coupling reactions,([2]) Ni- and Rh-catalyzed exocyclization methods,([3]) Ni- and Pd-catalyzed nucleophilic coupling reactions of alkynes([4]) and of alkyne-to-arylboronic acids,([5]) Ti-catalyzed tandem alkyne-epoxide-ethyl acetate coupling,([6]) and the ring-closing olefin metathesis by using Grubbs catalyst.([7]) Though catalytic conjugate addition of alkenes has been recognized as a potentially powerful synthetic methodology in forming tetrasubstituted olefins, generally applicable conjugate addition of simple olefins to α,β-unsaturated carbonyl compounds has been hampered by lack of reactivity of the olefin substrates and due to the formation of homocoupling and other byproducts. Chelate-assisted C–H insertion([8]) and cross coupling methods([9]) are among the most notable advances in catalytic coupling reaction of enones with simple alkenes. Ni-catalyzed conjugate addition and allylic substitution reactions of simple alkenes have also been reported recently.([10]) We recently discovered that the cationic complex [(C(6)H(6))(CO)(PCy(3))RuH](+)BF(4)(−) (1) is a highly effective catalyst precursor for the coupling reactions of arylketones and alkenes involving C–H activation.([11]) Herein we report a novel catalytic synthesis of tetrasubstituted olefins from the intermolecular conjugate addition reaction of simple olefins to α,β-unsaturated carbonyl compounds.